Pengaruh Waktu Infusa dan Suhu Air yang Berbeda Terhadap Aktivitas Antioksidan dan Vitamin C pada Infused Water Kulit Pisang - Manna Wassalwa (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
Effect of different time and water temperature of infusion on the antioxidant activity and vitamin C on banana peel infused water were studied. Antioxidant activity was performed by DPPH (1,1 diphenyl-1-picrylhydrazyl) radical scavenging method and concentration of vitamin C was determined using UV-Vis spectrophotometer method. The ANOVA test shown that the combination of time and water temperature of infusion gave a significant effect on the antioxidant activity and  vitamin C on banana peel infused water (p0,05). The highest concentration both of antioxidant with value 4,80 ppm and vitamin C value 9,75 ppm were obtained from sample of 37°C of water temperature with 120 minutes of infused duration. A positive correlation between concentration of each sample with their %inhibition was observed (r=0,99). IC50 value was measured of 3,63 ppm. It is shown that the sample exhibited a strong antioxidant DPPH radical scavenging activity.